The Influence of Government Accounting Standards, Information Technology, and Internal Control Systems on the Quality of Financial Reporting with Human Resource Competence as a Moderating Variable : (A Study of Judicial Work Units in Central Java, Indonesia) - Puttri Ayu Oktaviyani; Sri Nawatmi (Journal of Industrial Engineering & Management Research, 2026)
In general, the purpose of this study is to examine and analyze the role of each variable in an agency's financial reporting. Specifically, this study aims to analyze how compliance with and understanding of SAP can ensure consistency and transparency in the presentation of financial reports. To assess the extent to which the use of technology and accounting information systems accelerates the preparation process and improves the accuracy of reporting data. To understand how SPI functions to prevent errors and fraud, resulting in more valid and reliable reporting. To analyze whether employee skill levels and understanding can strengthen or weaken the relationship between SAP, Information Technology, and SPI variables on financial reporting quality. A quantitative approach was employed using primary data collected through questionnaires distributed to employees involved in financial management across 75 Judicial Work Units. Purposive sampling was applied based on respondents’ direct involvement in financial management. A total of 150 questionnaires were collected; however, 10 observations identified as outliers were excluded, resulting in a final sample of 140 respondents. The data were analyzed through validity tests, reliability tests, classical assumption tests, and hypothesis testing using Moderated Regression Analysis (MRA) with IBM SPSS Statistics version 26. The findings indicate that Government Accounting Standards, Information Technology, and Internal Control Systems have positive effects on Financial Reporting Quality. Human Resource Competence does not moderate the effects of Government Accounting Standards or Information Technology. However, it negatively and significantly moderates the effect of Internal Control Systems on Financial Reporting Quality. This finding suggests that as human resource competence increases, the contribution of internal control systems to ensuring financial reporting quality becomes weaker; conversely, employees with lower competence rely more heavily on the effectiveness of formal internal controls. In general, research findings on this topic indicate that Government Accounting Standards (SAP), Information Technology (IT), and Internal Control Systems (ISC) have a positive and significant impact on the quality of financial reporting. Adequate human resource (HR) competency has been shown to strengthen this positive relationship. The following are detailed conclusions from various literature and empirical research regarding the implementation of accrual-based SAP significantly improving transparency and accountability, which directly impacts the reliability of financial reporting quality.Optimal IT utilization accelerates the data presentation process and minimizes human error, resulting in more accurate and timely financial reporting.A well-designed system safeguards agency assets and ensures regulatory compliance, which has a strong and positive correlation with improved reporting quality. Employee expertise, educational background, and understanding of accounting are crucial. Competent HR can bridge the gap between SAP regulations and IT operations, empirically demonstrating the ability to strengthen the influence of systems and regulations on the preparation of quality financial reporting.